Akulturasi Budaya Kaili dan Nilai Pendidikan Islam dalam Tradisi Maulid Nabi di Palu Sulawesi tengah: Perspektif Sosiologi Pendidikan Islam - Zuhra Nur Fadhilah (Jurusan Tarbiyah,IAIN PALANGKARAYA, 2026)
This study aims to explain the process of internalizing values and their relevance for the younger generation, as well as to analyze the acculturation of Kaili culture and Islamic educational values in the tradition of the Prophet's Birthday in Palu City, Central Sulawesi. The study uses a qualitative method with a descriptive approach. study Bibliography. Data were collected through observation, interviews, and documentation of the Kaili community. Data analysis was carried out through the stages of data reduction, data presentation, and drawing conclusions. The results of the study indicate that the tradition of the Prophet's Birthday is the result of acculturation between the local Kaili culture and Islamic teachings that occurs harmoniously without eliminating the cultural identity of the community. This acculturation is reflected in the recitation of Barzanji, salawat, joint prayers, religious lectures, mutual cooperation, and various forms of social participation that accompany the implementation of the Birthday. This tradition contains religious, social, cultural, and moral values that are internalized through the process of teaching (ta'lim), habituation (ta'wid), and exemplary behavior (uswah) as the concept of Islamic education according to Al-Ghazali. In addition to strengthening love for the Prophet Muhammad, the tradition of the Prophet's Birthday also plays a role in shaping religious character, social awareness, and a spirit of community togetherness. This study found that the tradition of the Prophet's Birthday remains relevant for the younger generation because it can be a medium for character education and the inheritance of Islamic values that can be adapted to the times. Conceptually, this study confirms that local cultural traditions can function as non-formal Islamic educational institutions that contribute to the preservation of local wisdom and the strengthening of contemporary Islamic education.